Laffer curve as an example of excise income in Bosnia and Herzegovina - Vidimlić Selma (Megatrend Revija, 2024)
The aim of this research was to determine whether the theory of the Laffer curve can be applied in transition countries and what are the factors that can influence the relationship between the amount of individual tax and total collected revenues, that is, the elasticity of demand for cigarettes. As an example, the income from the sale of cigarettes in Bosnia and Herzegovina was taken. The research confirmed the existence of the Laffer curve in transition countries - the increase in the price of cigarettes as a result of increased excise taxes on cigarettes increased the tax revenues collected by the state, but up to the point when they started to decrease. As factors that can influence the calculation of the Laffer point, the peak in which the optimization of excise taxes is achieved, the elasticity of demand, inflation, tax morale shown through the percentage of the gray economy, the decline/growth of the population, the existence of substitutes, but also many others, which depend on a certain of the national economy, which was determined by studying previously published publications around the world, the methods of induction and deduction, analysis and synthesis, and general cognitive methods. This research can serve legislators when determining the optimal tax rate, but also the academic community when determining the interaction of demographic factors and total collected taxes.